Dance therapy in neurology - Šeduikienė , M.; Matonis , V. (Neurologijos seminarai, 2020)
A review of recent dance therapy publications shows that most of the research is devoted to the treatment of neurological disorders or the relief of symptoms through dance. Tango, salsa, rumba, marengue, ballet, and other dance forms are employed in the treatment of Parkinson’s disease, stroke, spinal cord injury, traumatic brain injury, etc. The increase in treatment cases shows the growing need for the healthcare system to use the possibilities of dance neurotherapy more effectively. The reviewed literature is divided into six sections: 1) increasing research into the therapeutic role of dance and growing popularity of dance therapy, 2) dance as an important neurotherapeutic means of motor, cognitive, emotional, spatio-visual, and social activation, 3) the role of dance in symptom alleviation in Parkinson’s disease, 4) limitations and possibilities of enlargement of neurologic dance therapy, 5) the impact of aesthetic experience of dance on the nervous system, and 6) the growth of the need for dance in healthcare programs. Surprisingly, this important area of investigation and treatment through dance has yet to be named. Taking into account both the scope and specifics of dance therapy activities, it would be appropriate to refer to specialized dance therapy for the treatment of neurological disorders as dance therapy in neurology (DTN). Many of the beneficial effects of dance have great potential to alleviate the symptoms of nervous system disorders and correspondingly expand the possibilities of DTN.
Keywords: dance therapy; neuroaesthetics; neurological disorders; Parkinson’s disease; dance intervention